Does Early Glasses Wear Improve Visual Outcome in OCA1A?. Issue 1 (2nd January 2021) - May, Laura; Merrill, Kimberly; Connett, John E.; Summers, C. Gail
ABSTRACT: Purpose : Oculocutaneous albinism type 1A (OCA1A), with lifelong absent melanin in skin, hair, and eyes, is the most severe type of albinism with greatest ametropia and poorest vision. We evaluated the relationship between age when spectacles were begun and visual outcome, in addition to status of refraction, in OCA1A. Methods : After IRB approval, a retrospective review of 70 consecutive charts of patients with OCA1A identified 24 fitting inclusion criterion of BCVA recorded at age 10–12 years. Exclusion criteria were those with other vision-threatening diagnoses and patients seen for a single visit. We recorded sex, age at beginning glasses, and refraction and BCVA at age 10–12 and most recent visit. Data were arbitrarily grouped by those initiating glasses at ≤ age 12 months and > age 12 months. Results : Regression analysis showed a larger degree of astigmatism was weakly associated with worse vision at age 10–12 years. A weakly positive relationship was found between poorer BCVA at last visit and older age at which glasses were initiated. All receiving glasses by age 1 and only half receiving glasses when older had improved visual acuity from age 10–12 years to last follow up. Conclusion : Additional study of a larger sample of this rare disorder is needed to determine if early glasses wear improves later BCVA.